MONITORING OF MICROBIOCENOSIS OF ORAL CAVITY IN EXPERIMENTAL OPIOID INTOXICATION IN CONDITIONS OF ANTIBIOTICS CORRECTION - F. B. Fik; Y. M. Fedechko (Ukrainian Medical Stomatological Academy, 2015)
Experimental animals of 6 weeks were administered morphine derivative - an opioid analgesic. A way to control the development of inflammatory processes of the oral cavity in the background of opioids impact and modeling method of antibiotics protective action including microbiological study of the microflora of dental plaque and soft tissues of the oral cavity, which includes microscopic and bacteriological studies. Opioid intoxication in rats predetermined change in behavior, body weight during 4-6 weeks reduced by 20%. During the second and third weeks of administration of opioid analgesics, edema, cyanosis and bleeding of mucous membranes were proved, especially at the free edge of the gums. In some species erosions were found on the vestibular mucosa. These changes were regressed due to the administration of ceftriaxone. Results of the study of species and quantitative composition of microflora indicates that oral experimentation was allocated mainly for saprophytic species of microorganisms. In the second week due to administration of analgesic for the same species, but 1.2 -1.8 times. Distinct changes in species and quantitative composition of the microflora were found due to the introduction of "nalbuphine" in the third week. It is important that pathogenic species were appeared - St. aureus, β- hemolytic streptococci, hemolytic Escherichia. In the fourth week the quantity of pathogenic species was significantly increased - St. aureus by 2 times and β- hemolytic streptococci by 3.5 times. Simultaneousl the number of saprophytic and opportunistic bacteria was increased by 1.8 - 3 times. Small amounts of Fungi Candida were identified. The administration of opioids for the experimental animals was continued during the fifth and sixth weeks, but they received antibiotic therapeutic doses. This led to significant changes of micro biocenosis of oral cavity. In the fifth week the number of St. aureus decreased by 3.5 times. In the sixth week these bacteria were not allocated. β- hemolytic, hemolytic streptococci and Escherichia were terminated after several ceftriaxone injections. In isolated bacterial isolates basic types of sensitivity to three antibiotics were studied: β-lactam first generation of cefazolin, third generation, and fluoroquinolon's drug ciprofloxacin. Microflora of oral cavity isolated at the beginning of the experiment was sensitive and highly sensitive ceftriaxone, except enterococci that are naturally resistant to β-lactams. However, at the end of the experiment the bacteria were isolatad that didn`t differ by biological characteristics from isolates at the beginning of the study, were less sensitive to this antibiotis. This is seen in authentic reduction zone diameter stunted growth of bacteria by standard discs with ceftriaxone. The degree of sensitivity of the same bacteria isolates didn`t change to antibiotics which were already injected - cefazolin and ciprofloxacin. This can be concluded that under the influence of ceftriaxone in experimental rats could happen selection bacterial options with hypersensitivity to this drug. So, due to long-term administration of opioids, the animals showed signs of opiate intoxication, withdrawal symptoms, accompanied by the development of inflammatory and necrotic processes in the oral cavity. Microorganisms capable of causing inflammatory processes appeared after increasing number of saprophytic bacteria and opportunistic species. Number of bacteria increased significantly in the development of opiate intoxication. Due to introduction of ceftriaxone, types of pathogens were eliminated, number of saprophytic bacteria decreased, but isolates showed weak sensitivity to ceftriaxone.